2021
DOI: 10.1080/08820538.2021.1900289
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Preferred Retinal Locus in Eyes with Central Vision Loss Secondary to Different Macular Lesions

Abstract: Objective: Preferred retinal locus (PRL) training has been applied to low-vision rehabilitation for patients with central vision loss (CVL). This study aimed to explore the characteristics of a natural PRL in eyes with different macular lesions. The data may be useful in customizing training programs.Methods: A total of 72 eyes with CVL were included and assigned into two groups. In group A, 29 eyes diagnosed with macular holes featured relatively sharp borders and small areas of lesions. In group B, 44 eyes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…However, the authors did not make personalized choices based on the patient's condition. Our previous study found that natural PRL may be optimal for patients with small and sharp scotomas, whereas patients with large and rough scotomas need to develop new training target 24 . In our study, four patients in whom the original PRL was used also improved visual performance, providing additional validation for our prior assertion that training targets should be selected individually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors did not make personalized choices based on the patient's condition. Our previous study found that natural PRL may be optimal for patients with small and sharp scotomas, whereas patients with large and rough scotomas need to develop new training target 24 . In our study, four patients in whom the original PRL was used also improved visual performance, providing additional validation for our prior assertion that training targets should be selected individually.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Choice of the Fixation Training Target(FTT): The selection of FTT was performed based on the microperimetry result and the following criteria: (1) PRL as FTT if the natural PRL is within an area of good retinal sensitivity and in a convenient location or (2) set an FTT with good retinal sensitivity, closest to the fovea, and choose the upper side of the natural PRL as far as possible, which presents the inferior visual field; this criterion is based on our extensive literature review and clinical experience spanning several years 23,24 .…”
Section: Methodsmentioning
confidence: 99%
“…The best personalized location of the TRL varies from person to person. While the patient has a larger scotoma, lower fixation stability, or PRL located away from the fovea, choosing a better TRL to conduct visual rehabilitation can significantly improve the visual function of patients with CVL [87] . The closer the distance between the fovea and TRL, the greater the maximum reading speed, reading acuity, and critical print size [67] .…”
Section: Preferred Retinal Locus Of the Patient With Central Vision Lossmentioning
confidence: 99%